Medical‐surgical nurses' perceived self‐confidence and leadership abilities as first responders in acute patient deterioration events. Issue 19 (7th January 2014) - Hart, Patricia L; Spiva, LeeAnna; Baio, Pamela; Huff, Barbara; Whitfield, Denice; Law, Tammy; Wells, Tiffany; Mendoza, Inocenica G
<x xml:space="preserve">Abstract</x> Aims and objectives To explore and understand medical‐surgical nurses' perceived self‐confidence and leadership abilities as first responders in recognising and responding to clinical deterioration prior to the arrival of an emergency response team. Background Patients are admitted to hospitals with multiple, complex health issues who are more likely to experience clinical deterioration. The majority of clinical deterioration events occur on medical‐surgical units, and medical‐surgical nurses are frequently the first healthcare professionals to identify signs and symptoms of clinical deterioration and initiate life‐saving interventions. Design A prospective, cross‐sectional, descriptive quantitative design using a survey method was used. Methods Nurses were recruited from an integrated healthcare system located in the south‐east United States. Nurses completed a demographic, a self‐confidence and a leadership ability questionnaire. Results One hundred and forty‐eight nurses participated in the study. Nurses felt moderately self‐confident in recognising, assessing and intervening during clinical deterioration events. In addition, nurses felt moderately comfortable performing leadership skills prior to the arrival of an emergency response team. A significant, positive relationship was found between perceived self‐confidence and leadership abilities. Age and certification status were significant predictors of nurses' leadership ability. Conclusion Although nurses felt moderately self‐confident and comfortable with executing leadership abilities, improvement is needed to ensure nurses are competent in recognising patients' deterioration cues and making sound decisions in taking appropriate, timely actions to rescue patients. Further strategies need to be developed to increase nurses' self‐confidence and execution of leadership abilities in handling deterioration events for positive patient outcomes. Relevance to clinical practice Educational provisions should focus on various clinical deterioration events to build nurses' self‐confidence and leadership abilities in handling clinical deterioration. Nurses should obtain national certification to increase their knowledge and clinical reasoning skills.